Kagandahan sa Panahon ng Globalisasyon - Claudio, Sylvia Estrada (Philippine Journal of Social Development; 2007, 2010)
This paper discusses gobalized cultural concepts of beauty as culled from locally published fashion and gossip magazines. It looks at the sexist, ageist, racist and consumerist constructions currently being mainstreamed. It also looks at the power dynamics that underpin these constructions by surfacing data on the transnational nature of local magazine publishing and the influence of western conceptions even on locally published material.  It then traces earlier conceptions of beauty and attractiveness by looking at classical love songs and the literature on beauty from the body of work of Philippine Psychology. Finally, the author challenges practitioners  of Philippine Psychology to actively participate in reconstructing and modernizing cultural conceptions of beauty and personhood that reaffirm the discipline’s goal of establishing more liberational theories and practices.